1997
DOI: 10.1093/jee/90.4.883
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Monoterpenoids to Western Corn Rootworm (Coleoptera: Chrysomelidae), Twospotted Spider Mite (Acari: Tetranychidae), and House Fly (Diptera: Muscidae)

Abstract: Acute toxicities of 34 naturally occurring monoterpenoids were evaluated against 3 important arthropod pest species; the larva of the western corn rootworm, Diabrotica virgifera virgifera LeConte; the adult of the twospotted spider mite. Tetranychus urticae Koch; and the adult house fly. Musca domestica L. Potential larvicidal or acaricidal activities of each monoterpenoid were determined by topical application, leaf-dip method, soil bioassay, and greenhouse pot tests. Phytotoxicity was also tested on a corn p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
129
2
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(138 citation statements)
references
References 21 publications
(23 reference statements)
4
129
2
3
Order By: Relevance
“…Cages were and Muller 1976, Andrews et al 1980, Watanabe et al 1990, and Ikawa et al 1992. Lee et al (1997) and Rice and Coats (1994) are currently investigating structure-activity relationships for monoterpenoids applied to various arthropods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cages were and Muller 1976, Andrews et al 1980, Watanabe et al 1990, and Ikawa et al 1992. Lee et al (1997) and Rice and Coats (1994) are currently investigating structure-activity relationships for monoterpenoids applied to various arthropods.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, at concentrations below the calculated LCsos, all 4 compounds reduced oviposition, and 3 of the compounds increased movement. Lee et al (1997) reported that most of the 30 monoterpenoids they tested for activity against the twospotted spider mite, Tetranychus urlicae Koch, exhibited some degree of acaricidal activity, especially the alcohols, phertols, and ketones. Larson and Berry (1984) examined T. urlicae fecundity and development on peppermint, Mentha piperita, leaves that differed in monoterpene content, but were unable to correlate monoterpene content of leaves with either fecundity or development.…”
mentioning
confidence: 99%
“…Several monoterpenes are widely used in the agriculture, cosmetic, and food industries, and as a general antiseptic in medical practice (Aeschbach et al, 1994;Lee et al, 1997;Manou et al, 1998). Most of the aroma from citrus fruit oil, cherries, and mint is due to the high content of monoterpenes, but they have no nutritional value because they are exclusively vegetable (Serrano et al,2006).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the terpenoid mixture is enhanced by the presence of various functional groups, stereochemistry, and carbon skeletal structures (1). The toxicity of essentials oils and their terpenoid constituents to insects has been the focus of several studies (2)(3)(4). While these terpenoids have been shown to be toxic to insects, their precise mechanism of how they exert this toxic action is not fully understood.…”
mentioning
confidence: 99%